VALUATION OF WAQF ASSETS ACCORDING TO PSAK 412 TO REALIZE ACCOUNTABILITY - MAQASID AL-SHARIAH PERSPECTIVE - Erny, Erny Arianty; Hendra Pratama, Raditya; Aprilia, Rachma (Universitas Islam Negeri Alauddin Makassar, 2025)
The purpose of this study is to analyze the assessment methods and presentation of waqf assets in accordance with PSAK 412, as managed by the Nazir YSU, and to examine the relationship between the implementation of PSAK 412 and the accountability – Maqashid Sharia Perspektif. This research employs a qualitative method using secondary quantitative data supported by interviews and direct observations of the waqf assets. The results indicate that several waqf assets have not been recorded, financial reports are incomplete and do not fully comply with PSAK 412. The analysis results show that the valuation and presentation of cash waqf assets have been implemented according to standards, and the accounting treatment of waqf assets transferred to the mauquf alaihi complies with the standards. However, the accounting treatment of physical waqf assets still managed by the foundation needs improvement to meet accounting standards in terms of both valuation and presentation. The implementation of PSAK 412 clearly realizes accountability from the perspective of Maqashid Sharia, ensuring the protection of religion, intellect, life, wealth, and lineage